Analisis Efektvitas Manajemen Operasional Teaching Factory “Skala Boga” Di Jurusan Kuliner SMK Negeri 1 Lamongan - Delya Anggi Ratnaningtyas; Sri Handajani; Any Sutiadiningsih; Nurul Farikhatir Rizkiyah (EduInovasi: Journal of Basic Educational Studies, 2025)
The purpose of this research is to analyze the operational management of the Teaching Factory "Skala Boga" in the Culinary Department of SMK Negeri 1 Lamongan. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The research subjects include the head of the department, Teaching Factory managing teachers, and culinary students of SMK Negeri 1 Lamongan. The data were analyzed through data reduction, data presentation, and conclusion/verification. The results indicate that the implementation of operational management has been carried out fairly well. (1) Planning covers aspects of human resources, production, finance, and marketing, all of which have been well structured. (2) Organizing includes a clear organizational structure and effective resource management. (3) In the actuating aspect, human resources have performed their duties and responsibilities effectively, production meets standard requirements, financial records are detailed, and marketing has achieved a fairly broad reach. (4) Supervision is conducted by teachers and coordinators, including regular financial audits and marketing evaluations.